Guidance and Counseling Program for Marriage and Family Readiness for MA Students - Resnawati Agustiani; Abas Mansur Tamam (Program Studi Bimbingan Konseling dan Pendidikan Islam, 2020)
The purpose of this study is to produce guidance and counseling programs for marriage and family readiness for students in Madrasah Aliyah (MA). Guidance and Counseling Program Marriage and family readiness is a developmental task for students to minimize divorce rates. The research method used in this study is qualitative field research. Data collection tool through observation, interviews, and documentation. The results of the program formulation and marriage and family readiness counseling for MA students were tested for validity through a Focus Group Discussion (FGD) with 4 experts namely: religious experts, linguists, psychologists, and education experts. The results of this study can describe that the guidance and counseling program for marriage and family readiness at Al-Amin Islamic Boarding School in a structured manner does not yet exist, the implementation at Al-Amin Islamic Boarding School is carried out in the Tsalasa Tsanawi class. Through the study of the classic Uqudulujein. Whereas at the Office of Religious Affairs (KUA) the guidance and counseling program for marriage and family readiness for prospective brides is held once on Wednesday, starting at 09: 00-12: 00. Through sakinah family foundation module. This marriage preparation guidance and counseling program for Madrasah Aliyah (MA) students is based on Permendikbud No. 111 of 2014, through basic services that refer to readiness in the field of personal services (Jasadiyah), social fields (Ijtimaiyah), learning fields (Ilmiyah) and career fields (Maaliyah)AbstrakTujuan dari penelitian ini adalah menghasilkan program bimbingan dan konseling untuk kesiapan perkawinan dan keluarga bagi siswa Madrasah Aliyah (MA). Program Bimbingan dan Konseling Kesiapan perkawinan dan keluarga merupakan tugas perkembangan mahasiswa untuk meminimalkan angka perceraian. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian lapangan kualitatif. Alat pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil perumusan program dan penyuluhan kesiapan nikah dan keluarga untuk mahasiswa MA diuji validitasnya melalui Focus Group Discussion (FGD) dengan 4 orang ahli yaitu: ahli agama, ahli bahasa, psikolog, dan ahli pendidikan. Hasil penelitian ini dapat menggambarkan bahwa program bimbingan dan konseling perkawinan dan kesiapan keluarga di Pondok Pesantren Al-Amin secara terstruktur belum ada, implementasi di Pondok Pesantren Al-Amin dilaksanakan di Pondok Pesantren Tsalasa Tsanawi. kelas. Melalui studi tentang Uqudulujein klasik. Sedangkan di Kantor Urusan Agama (KUA) program bimbingan dan penyuluhan untuk kesiapan perkawinan dan keluarga bagi calon pengantin dilakukan satu kali pada hari Rabu, mulai pukul 09.00-12.00. Melalui modul yayasan keluarga sakinah. Program bimbingan dan konseling persiapan nikah bagi siswa Madrasah Aliyah (MA) ini berpedoman pada Permendikbud Nomor 111 Tahun 2014, melalui pelayanan dasar yang mengacu pada kesiapan di bidang pelayanan pribadi (jasadiyah), bidang sosial (Ijtimaiyah), bidang pembelajaran ( Ilmiyah) dan bidang karir (Maaliyah)